Ambientações de horror: proposta poética em artes visuais - Zambiazzi, Dayvison (2017)
The research investigates the potential of artistic ambiences that invoke the imaginary of the horror films, and that moving between approach and repulsion, make the subject, sometimes spectator, now participant of the artist 's proposal. It is believed that by means of video installations or ambiences, the research allows the creation of works capable of giving the spectator encounters with sensations of horror, or synesthesias similar to those of a horror film. The research goes through thinking about sculpture, installation, appropriation of horror movie scenes, video installation and ambiences. To this end, authors related to the horror are being investigated, such as Noël Carroll, Howard Phillips Lovecraft, Stephen King, and authors and researchers related to the universe of art like Arthur Danto, Georges Didi-Huberman, Edmund Burke. Faced with the relationship between visual arts, cinema and the space occupied by the spectator, research contributes to broadening the context of art and the context of the researcher's performance.